Outcomes of Second Combination Antiretroviral Therapy Regimens Among HIV-Infected Persons in Clinical Care: A Multicenter Cohort Study - Napravnik, Sonia (Mary Ann Liebert, Inc., 2013)
Data on the effectiveness of second-line combination antiretroviral therapy (cART) are limited. We evaluated virologic outcomes of second cART in a multicenter cohort collaboration. The study population initiated first and second modern cART between 1996 and 2010. The second cART required a switch in at least the anchor agent of first cART. We evaluated time to virologic failure of second cART and factors associated with greater risk of failure using multivariable Cox proportional hazards models. Of 488 patients who switched to second-line cART, 67% were black and 32% were women. The median HIV-1 RNA at second cART initiation was 9,565 copies/ml [interquartile range (IQR); 123, 94,108]. The time to virologic failure of second cART was longer if HIV-1 RNA was undetectable at switch (p=0.001), although 12% and 17% of patients with undetectable and detectable HIV-1 RNA experienced virologic failure within 6 months of second cART initiation, respectively. A lower CD4 cell count at second cART initiation was associated with a greater risk of virologic failure. Failure rates decreased in more recent calendar years [adjusted relative hazard of 0.40 comparing 2008 to 2010 with 1996 to 1998 (95% confidence interval; 0.15, 1.00)]; however, type of anchor agent was not associated with failure. In conclusion, virologic failure of second cART was less likely if patients switched with undetectable HIV-1 RNA, although risk of early failure was similar. The effectiveness of second cART regimens improved over calendar time and was independent of the anchor agent in the regimen.